Correlation between Children with Asthma and Mean of Academic Marks in Elementary School - , DAVEGA ANDRATAMA, dr. Sumadiono,Sp.A(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Asthma is a chronic disease that mostly occurred in children and burdens the children with absenteeism compared to any other chronic conditions. A child with asthma often has difficulties to deal with how he or she manages, treats, and avoids asthma attacks. This can result in difficulties to concetrate in their school study that may affect academic achievement. Objectives: The purpose of the authors conducted this research was to study the relationship between allergic asthma experienced by children with academic accomplishments achieved in their respective schools. Method: The study design used in this study is crosssectional. Determination of asthma diagnosis is made through questionnaire. The research was conducted in elementary schools in the district of Sleman, Yogyakarta from January 2013 until February 2013. Sampling is done with cluster random sampling. Measurement tool used in this study is in the form of a report card to obtain the grade or marks of students who have asthma and do not have asthma. Data analysis uses independent sample t-test. Results: The results of the marks on six academic subjects were taken from civilization, bahasa indonesia, mathematics, science, social science, and arts. The mean result for civilization subjects in asthma group is 73.27 while in non asthma is 74.22 with p value = 0.53. The mean of bahasa indonesia marks in asthma group is 75.27 while in non asthma group is 75.45 with p value = 0.91. The mean of mathematics marks in asthma group is 71.62 while in non asthma group is 74.18 with p value = 0.14. The mean of science marks in asthma group is 73.32 while in non asthma group is 74.18 with p value = 0.55. The mean of social science marks in asthma group is 73.17 while in non asthma group is 75.6 with p value = 0.07. The mean of arts marks in asthma group is 75.82 while in non asthma is 76.13 with p value = 0.67. Conclusion: In this study, there is no significant difference in academic marks achieved between asthmatic and non-asthmatic students.